As-built data acquisition and its use in production monitoring and automated layout of civil infrastructure: A survey. Issue 2 (April 2015) - Son, Hyojoo; Bosché, Frédéric; Kim, Changwan
Highlights Access to reliable 3D as-built data is a critical issue in civil infrastructure. Applications to production monitoring and automated layout are discussed. Research on applications of as-built data in the civil engineering field is reviewed. State-of-the-art and other developments in as-built data analysis are surveyed. Unsolved problems and challenges for future improvements in this field are discussed.